Studies on population buildup of Scutellonema bradys in Dioscorea species - Oluwatayo, J.I.; Asiedu, Robert; Adesiyan, S.O. (2011)
Field and storage evaluation of four yam cultivars TDr 131 (Dioscorea rotundata), TDa 85/00257 (D. alata), Igangan (Dioscorea cayenensis), TDe 3041 (D. esculenta) in intercrop with three other crops, cocoyam (Xanthosoma sagittifolium), ginger (Zingiber oficinale) and maize (Zea mays) to the occurrence and abundance of the yam nematode, scutellonema bradys showed signiicant variation in dry rot incidence which increased throughout the period of storage. There was a signiicant positive correlation (r = 0.77; P<0.05) between soil nematode population and number of nematodes extracted from the peels of the tubers. Intercropping susceptible yam cultivars with maize, ginger, and cocoyam signiicantly (P<0.05) reduced soil nematode population by 38%, 42%, and 54%. Data analysis showed that fewer nematodes were able to survive on tubers in the intercropped plots as compared to the sole plots. Nematode populations increased 14-foldin the untreated plots and 2-fold in the intercropped plots.